Inference or enaction data set - Dunbar, R; Carney, J; Wlodarski, R (University of Oxford, 2014)
This spreadsheet contains the results of the 'Inference or Enaction' experiment on the narrative processing of other minds. It is being made publicly available as part of the open access policy in European Research Council funded research, grant number 295663.